The impact of using gonadotropin-releasing hormone agonist for triggering final oocyte maturation in antagonist-treated intracytoplasmic sperm injection cycles on women at high risk of developing ovarian hyperstimulation syndrome. Issue 3 (August 2016) - Elnassery, Noura S.; Abuhamila, Fouad A.
Abstract : Objective: The study aimed to assess the impact of gonadotropin-releasing hormone (GnRH) agonist trigger in GnRH antagonist intracytoplasmic sperm injection cycles. Study design: It was a retrospective, cohort study. Patients and methods: Participants were assigned to two groups: group 1 included 257 women at risk of developing severe ovarian hyperstimulation syndrome (OHSS), and group 2 included 525 women with a lower risk of developing severe OHSS. All participants were subjected to the GnRH antagonist protocol triggered with GnRH agonist in group 1 and with human chorionic gonadotropin in group 2. Patients were then subdivided into those who transferred their embryos on day 3 and those who transferred their embryos on day 5. Results: The main outcomes were pregnancy rate, clinical pregnancy rate, implantation rate, and OHSS rate in each group. Group 1 had higher number of MII oocyte collection, higher number of frozen embryos, and higher number of cycles with available embryos for cryopreservation. A lower pregnancy rate, clinical pregnancy rate, and implantation rate were achieved in group 1, with significantly less moderate/severe OHSS, especially in patients who transferred their embryos on day 5. Conclusion: GnRH agonist trigger should be the protocol of choice as regards its benefit in preventing OHSS, with special rescue measures for the luteal phase.